A Novel Antenna Placement Algorithm for Compressive Sensing MIMO Radar - Eisele, Bastian; Bereyhi, Ali; Ullmann, Ingrid; Müller, Ralf (2023 IEEE Radar Conference (RadarConf23), 2023)
In colocated compressive sensing MIMO radar, the measurement matrix is specified by antenna placement. To guarantee an acceptable recovery performance, this measurement matrix should satisfy certain properties, e.g., a small coherence. Prior work in the literature often employs randomized placement algorithms which optimize the prior distribution of antenna locations. The performance of these algorithms is suboptimal, as they can be easily enhanced via expurgation. In this paper, we suggest an iterative antenna placement algorithm which determines the antenna locations deterministically. The proposed algorithm locates jointly the antenna elements on the transmit and receive arrays, such that the coherence of the resulting measurement matrix is minimized. Numerical simulations demonstrate that the proposed algorithm outperforms significantly the benchmark, even after expurgatio
Keywords: Compressive sensing; MIMO radar; Antenna placement; coherence